2014
DOI: 10.1016/j.ophtha.2013.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Changing Incidence of Lens Extraction over 20 Years

Abstract: Objective Investigate trends in incidence of lens extraction over the past twenty years. Design Longitudinal population-based cohort study. Participants Persons who participated in the Beaver Dam Eye Study. Methods Eligible persons 43–84 years of age living in the city or township of Beaver Dam, Wisconsin were recruited in 1987–1988. Participants were followed up every five years in 1993–1995, 1998–2000, 2003–2005, and 2008–2010 after the baseline examination in 1988–1990. Examinations consisted of ocula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 25 publications
2
36
0
Order By: Relevance
“…Cataracts are highly prevalent with advancing age 218 and the incidence of cataract surgery is increasing in many developed countries. 219 The benefits cataract surgery has on functional vision and quality of life have been well documented for community-dwelling ageing individuals, 220,221 including the oldest-old. 222 This latter study showed that those 90 years of age or older were the most unsatisfied with their vision prior to surgery and that 79% fared better in their activities of daily living after the surgery.…”
Section: Clinical Considerationsmentioning
confidence: 99%
“…Cataracts are highly prevalent with advancing age 218 and the incidence of cataract surgery is increasing in many developed countries. 219 The benefits cataract surgery has on functional vision and quality of life have been well documented for community-dwelling ageing individuals, 220,221 including the oldest-old. 222 This latter study showed that those 90 years of age or older were the most unsatisfied with their vision prior to surgery and that 79% fared better in their activities of daily living after the surgery.…”
Section: Clinical Considerationsmentioning
confidence: 99%
“…The trend observed in the Malaysian CSR reflects a reduction in cataract surgery in patients who are cataract blind and an increase in those who have cataract visual impairment. On the other hand, health care demands in developed countries such as the United States, 3 Australia, 4 and Sweden 5 have shown an increasing trend for cataract surgery in people with VA better than 6/12, indicating very early or no cataract.…”
Section: Preoperative Visual Acuitymentioning
confidence: 99%
“…The World Health Organization has set a minimum rate required to combat cataract blindness at 3000 surgeries per million people per year. 2 Developed countries such as the United States, 3 Australia, 4 and Sweden 5 have exceeded the recommendation (ie, between 7000 and 11,000 surgeries per million people). On the other hand, developing countries with limited resources but a higher burden of cataract blindness have lower rates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, diagnosis-related group-based (DRG) reimbursement does not include cataract surgery and vitreoretinal surgery in the same procedure: our clinical goal is to only take our patients to the surgical theatre once in patient-orientated surgery. [2][3][4] Historically, the most common surgical platforms for vitrectomy surgery, since its introduction in 1997, have been the Alcon Accurus or DORC platform systems. 5,6 However, when we pioneered 23-gauge surgery, we experienced an increased rate of retinal detachment following macular surgery.…”
mentioning
confidence: 99%